2011
DOI: 10.1038/nmeth.1636
|View full text |Cite
|
Sign up to set email alerts
|

A large-scale method to measure absolute protein phosphorylation stoichiometries

Abstract: The underlying functional role of protein phosphorylation is impacted by its fractional stoichiometry. Thus, a comprehensive strategy to study phosphorylation dynamics should include an assessment of site stoichiometry. Here, we developed an integrated method that relies on phosphatase treatment and stable isotope labeling to determine the absolute stoichiometries of protein phosphorylation on a large-scale. This approach requires the measurement of only a single ratio relating phosphatase- and mock-treated sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
260
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(271 citation statements)
references
References 42 publications
(50 reference statements)
9
260
2
Order By: Relevance
“…Several high throughput screens have indicated that the N-terminal end of Arg82 is phosphorylated at positions in close proximity (33)(34)(35). We tested whether these modifications have any implication for cell growth or transcriptional regulation of arginine-regulated promoters in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Several high throughput screens have indicated that the N-terminal end of Arg82 is phosphorylated at positions in close proximity (33)(34)(35). We tested whether these modifications have any implication for cell growth or transcriptional regulation of arginine-regulated promoters in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Mass spectrometry has been used to examine phosphorylation stoichiometry in large scale studies (14,16,17). One central issue that is addressed by these approaches is that post-translationally modified peptides and their corresponding unmodified counterparts have varying ionization efficiencies, and thus, they cannot be directly compared.…”
mentioning
confidence: 99%
“…Furthermore, it is unclear how the estimates behave when the changes in PTM status across conditions are small. In the context of phosphorylation, these challenges can be addressed by treating an identical stable isotope-labeled sample with a phosphatase and measuring and comparing the increased abundance of the unphosphorylated peptide (17). The percent increase provides a measurement of the stoichiometry of a phosphosite that circumvents the need for enrichment and the requirement for a change in the level of a PTM site.…”
mentioning
confidence: 99%
“…Finally, another elegant strategy used a combination of deuteroformaldehyde/formaldehyde stable isotope chemical labeling and alkaline phosphatase treatment [12]. The sample of interest was divided into two aliquots for treatment with phosphatase and phosphatase-free control.…”
Section: Introductionmentioning
confidence: 99%
“…Following differential chemical labeling of free amines with stable isotopes, both aliquots were recombined. Mass spectrometric analysis of the recombined mixture revealed the degree of phosphorylation by measuring the signal increase from the dephosphorylated peptide of the corresponding phosphopeptide [12]. However, this is a phosphorylation-centric method, which cannot be applied to covalent chemical modifications.…”
Section: Introductionmentioning
confidence: 99%